Meningkatkan Customer Satisfaction melalui Service Excellence di Hotel Holiday Inn Jakarta Kemayoran - Cici Sri Kemala; Parlagutan Silitonga (BULLET : Jurnal Multidisiplin Ilmu, 2023)
The hotel industry is one of the fastest growing industries in Indonesia, along with the development of domestic and international tourism. Some of property owned by Indonesian citizens with Indonesian legal entities, in general, mainly three-star to five-star hotels. How ever the operational is managed by hotel chains such as Hilton, Intercontinental and Accor. This study aims to increase customer satisfaction by corporate credibility and brand credibility mediated by service excellence. The analysis method used in this study is PLSSEM with software SmartPLS3.0. The population and sample in this study were customer staying at Holiday Inn Jakarta Kemayoran Hotel on their first visit or more. Accidental sampling through the distribution of google form is a sampling technique consisting of 150 respondents. This study shows result with good values and has a significant positive influence between each variable both directly and indirectly.